Effect of salt spray environment on the corrosion behavior of PCB-HASL and PCB-ENIG - YI Pan; DING Kang-kang; SONG Wei-feng; DONG Chao-fang; LI Xiao-gang; WU Jun-sheng; XIAO Kui (工程科学学报)
The corrosion behavior of hot air solder level printed circuit boards(PCB-HASL) and electroless nickel immersion gold printed circuit boards(PCB-ENIG) in salt spray test was studied by electrochemical impedance spectroscopy. The corrosion product morphology,composition and coating failure mechanism were observed by stereo microscopy,scanning electron microscopy and energy-dispersive X-ray spectroscopy. The results show that PCB-HASL and PCB-ENIG suffer severe corrosion in high salt spray environment. Localized corrosion occurs first in the Sn plating layer,and then almost entire surface corrosion occurs,similar to uniform corrosion. PCB-ENIG mainly generates microporous corrosion. In the PCB-HASL corrosion process,Cl- promotes the corrosion of the Sn layer,then a large amount of corrosion product gradually forms and covers the Sn surface,it makes the corrosion rate reduce.In the PCB-ENIG corrosion process,a thin liquid layer containing Cl- electrolyte forms in micropores,and galvanic coupling between gold and nickel constitutes,which accelerates Ni corrosion. The Cu base directly exposes in the adverse environment after Ni suffers serious corrosion,finally leading to electronic component failure.